Analysis of the Advantages and Disadvantages of Using MikroTik in Computer Network Implementation - Khazanatul Asrar; Dirja Nur Ilham; Muhammad Khoiruddin Harahap; T. Sukma Achriadi Sukiman; Nurul Hamdi (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid growth of information technology has increased the demand for reliable, secure, and efficient computer network infrastructures. MikroTik is widely adopted as a cost-effective networking solution, particularly for small to medium-scale networks. This study aims to analyze the advantages and disadvantages of using MikroTik in computer network implementations based on previous empirical studies. This research employs a literature review method by analyzing more than fifteen scientific articles published within the last five years. The reviewed studies focus on bandwidth management, firewall configuration, network security, Quality of Service (QoS), and network monitoring using MikroTik RouterOS. The findings indicate that MikroTik offers several advantages, including flexible configuration, comprehensive RouterOS features, effective bandwidth management, and relatively low implementation costs. However, several limitations were identified, such as configuration complexity, non-optimal default security settings, performance degradation under high traffic loads, and limited scalability for large enterprise networks. With proper configuration and the integration of additional security mechanisms, MikroTik remains an effective and efficient solution for small to medium-scale network implementations.